Neuromonitoring modalities predicting neurological impairment in pediatric congenital heart disease: a systematic review - Van Loo, Liselotte; Cools, Bjorn; Dereymaeker, Anneleen; Jansen, Katrien (Frontiers in Neurology, 2024)
The increased risk of neurodevelopmental impairment in children with congenital heart disease (CHD) has been established, but the search for targeted neurological predictors of adverse outcome is ongoing. This systematic review reports on the utility of three functional neuromonitoring modalities, Near-infrared Spectroscopy (NIRS), electroencephalography (EEG) and biochemical biomarkers, in predicting either clinical neurodevelopmental outcome or structural brain abnormalities after pediatric CHD surgery. Medline, Embase, CENTRAL, Web of Science, clinicaltrials.gov and ICTRP were systematically searched for eligible articles. Original research articles, written in English, published before November 2023 and reporting on perioperative NIRS, EEG or biomarkers and their association with clinical neurodevelopmental outcome or neuroimaging in children <17 years undergoing surgery for CHD were included. The search yielded 11,367 citations, of which 40 papers were included in the final review: sixteen articles (n = 908 cases) reported on NIRS, twelve (n = 1,163) on EEG and fifteen (n = 903) on biochemical biomarkers. Three papers reported on a combination of modalities. Median age at time of surgery was 9 (IQR 7–57) days. Postoperative MRI was performed before discharge at varying timepoints. Median age at clinical outcome assessment was 15 (IQR 12–24) months. Limited evidence supports an association of cerebral oxygen extraction, cerebral desaturation and cerebral autoregulation with outcome, but there was significant heterogeneity in results. Perioperative electroencephalographic ictal discharges and abnormal background were associated with impaired neurological outcome and abnormal neuroimaging. Numerous biochemical biomarkers have been reported but showed no consistent relationship with outcome, except for lactate, which could serve as a predictor of poor outcome. There is a need for larger homogeneous cohorts of children with CHD to determine which perioperative modalities might serve as predictors of neurodevelopmental outcome or neuroimaging abnormalities.Systematic review registrationhttp://www.crd.york.ac.uk/PROSPERO, CRD42023479344